The Relationship Between Communication in the Family and Early Childhood Language Development - Ali Afrizal; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the low language development of children aged 3-4 years in Air Tawar Barat Village, Padang City. This is suspected to be poor communication in the family with children. This study aims to determine the relationship of communication in the family with the language development of early childhood in Air Tawar Barat Village, Padang City. This research uses a correlational quantitative approach. The study population was 54 mothers with a sample of 27 mothers. Sampling in the study used a simple random sampling technique, namely random sampling from a portion of the population. Research findings (1) communication in the family is categorized as low (2) language development of early childhood is categorized as low (3) there is a significant relationship between communication in the family and language development of early childhood in Air Tawar Barat Village, Padang City. There is a significant relationship between communication in the family and the language development of early childhood in the Village of Air Tawar Barat, Padang City.